1989
DOI: 10.1080/00288330.1989.9516366
|View full text |Cite
|
Sign up to set email alerts
|

Benthos associated with two New Zealand coastal outfalls

Abstract: The benthic ecological impacts of 2 New Zealand ocean outfalls were studied. They are the country's largest (discharging 0.8 m 3 s -1) at Hastings, and longest-established (operating since 1965 and with a present discharge of 0.28 m 3 s -1 ) at Gisbome. Both discharge essentially biodegradable domestic and food-processing-industry wastes. Samples were collected about each outfall and analysed for particle size, oil and grease, readily oxidisable carbon (ROC), total Kjeldahl nitrogen (TKN), volatile solids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…With increasing distance, species numbers increase and high individual abundances decline. Although such changes in species and abundance have been observed around other local outfalls (Knox & Fenwick 1981;Roper et al 1989) the benthos near Tauranga outfall was not affected in this way. This was presumably because in this situation physical sediment characteristics (i.e., PS and sorting), rather than the discharge, were more important in determining abundances of taxa and individuals.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…With increasing distance, species numbers increase and high individual abundances decline. Although such changes in species and abundance have been observed around other local outfalls (Knox & Fenwick 1981;Roper et al 1989) the benthos near Tauranga outfall was not affected in this way. This was presumably because in this situation physical sediment characteristics (i.e., PS and sorting), rather than the discharge, were more important in determining abundances of taxa and individuals.…”
Section: Discussioncontrasting
confidence: 65%
“…The higher mud levels up to 400 m to the west of the outfall are consistent with the net flow in this direction. Roper et al (1989) found a similar change in the sediments near the Gisborne outfall, where inorganic material settling out of the effluent increased sediment muddiness. It is possible, however, that mud deposits about the Tauranga outfall are natural, and unrelated to the discharge.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, the presence of the highly abundant T d ulongii is likely to increase, not decrease, the availability of metals to higher trophic level consumers such as fish, which may prove to be another significant impact of species that are introduced by ships' ballast waters. The polychaetes Capjtella 'capitata' and Heterornastus filiformis are opportunistic species capable of exploiting sewage-contaminated conditions (Grassle & Grassle 1976, Roper et al 1989. Both are widely distributed in many marine and estuarine habitats in Australia.…”
Section: Discussionmentioning
confidence: 99%